1998
DOI: 10.1111/j.1346-8138.1998.tb02419.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pediatric Case of Atypical Mycobacterium avium Infection of the Skin

Abstract: We report a case of cutaneous atypical mycobacteriosis in a 12-year-old healthy girl due to Mycobacterium avium. The cutaneous symptoms were three well-defined subcutaneous nodules on both buttocks and on the posterior surface of the left thigh. One had a fistulous opening on the skin surface. Histopathological examination revealed epithelioid cell granulomas surrounded by dense lymphocytic infiltration and acid-fast bacteria were seen with modified periodic acid-carbol fuchsin staining. Using Ogawa's medium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Additional experiments are needed to investigate this hypothesis. MAC can also enter the host by the intradermal route through cuts and skin punctures (53,54). Experimental work showed that intradermal bacillus administration resulted in infection of cervical and/or axillary lymph nodes in both BALB/c and nude mice, suggesting that skin lesions may also be responsible for the cervical lymphadenitis seen in humans (53).…”
Section: Discussionmentioning
confidence: 99%
“…Additional experiments are needed to investigate this hypothesis. MAC can also enter the host by the intradermal route through cuts and skin punctures (53,54). Experimental work showed that intradermal bacillus administration resulted in infection of cervical and/or axillary lymph nodes in both BALB/c and nude mice, suggesting that skin lesions may also be responsible for the cervical lymphadenitis seen in humans (53).…”
Section: Discussionmentioning
confidence: 99%
“…MAC has been shown to present as pulmonary infections in immunocompetent patients including elderly women and smokers, as well as immunocompromised individuals who have undergone organ transplantation or with inheritable defects in IFN-␥ (10,14). Cutaneous manifestations of MAC in immunocompetent individuals also occur, especially in children (15,16). All of these manifestations of MAC have in common infiltration by mononuclear cells and granuloma formation.…”
mentioning
confidence: 99%
“…The MAI complex may infect virtually any tissue, and surgical excision of abscesses has been reported from cervical lymphatic [24], pulmonary [25], cutaneous [26], tenosynovial [27,28], meningeal [29], and paranasal sinus [30] sites. In our case, re-operation was decided against initially, despite clinical deterioration, because the patient had not received a multidrug regimen effective against MAI until that time and, ultimately, because of the patient's rapid improvement once effective treatment was instituted.…”
Section: Discussionmentioning
confidence: 99%